Cold atmospheric pressure plasma and low energy electron beam as alternative nonthermal decontamination technologies for dry food surfaces: A review. (July 2018) - Hertwig, Christian; Meneses, Nicolas; Mathys, Alexander
Abstract: Background: Dry food products are often highly contaminated, and dry stress-resistant microorganisms, such as certain types of Salmonella and bacterial spores, can be still viable and multiply if the product is incorporated into high moisture food products or rehydrated. Traditional technologies for the decontamination of these products have certain limitations and drawbacks, such as alterations of product quality, environmental impacts, carcinogenic potential and/or lower consumer acceptance. Cold atmospheric pressure plasma (CAPP) and low energy electron beam (LEEB) are two promising innovative technologies for microbial inactivation on dry food surfaces, which have shown potential to solve these certain limitations. Scope and approach: This review critically summarizes recent studies on the decontamination of dry food surfaces by CAPP and LEEB. Furthermore, proposed inactivation mechanisms, product-process interactions, current limitations and upscaling potential, as well as future trends and research needs for both emerging technologies, are discussed. Key findings and conclusions: CAPP and LEEB are nonthermal technologies with a high potential for the gentle decontamination of dry food surfaces. Both technologies have similarities in their inactivation mechanisms. Due to the limited penetration depth of both technologies, product-process interactions can be minimized by maintaining product quality. A first demonstrator with Technology Readiness Level (TRL) 7 for LEEB has already been introduced into the food industry for the decontamination of herbs and spices. Compared with LEEB, CAPP is at the advanced development stage with TRL 5, for which further work is essential to design systems that are scalable to industrial requirements. Highlights: Decontamination of dry food surfaces is a major challenge in food industry. Cold plasma & low energy electron beam are promising innovative solutions. Product-process interactions can be minimized. Cold plasma is at the advanced development stage for food applications. Low energy electron beam has been already introduced into the food industry.